"Wandering Spleen" with lymphomatous involvement - DEDE, FUAT (My University, 2023)
Wandering spleen is a rare condition caused by either lack or the laxity of ligaments, which results malposition in the lower abdomen or pelvis. FDG PET/CT is the cornerstone of the staging procedures in the management of lymphomas leading to upstaging and picking up occult lesions in the spleen and extranodal sites. Herein, we reported initial staging 18F-FDG PET/CT findings of a woman with Hodgkin lymphoma whose spleen was absent in normal position and multiple intense heterogenous hypermetabolism in a pelvic mass raised a suspicion of wandering splenic involvement. The confirmation was made with selective spleen SPECT/CT images thereafter.
Keywords: Hodgkin lymphoma; FDG PET/CT; wandering spleen; selective spleen scintigraphy